IMPLEMENTING THE THEORY OF IJARAH ON PROOFREADING SERVICES: A CASE STUDY AT AT IAIN ZAWIYAH COT KALA LANGSA, INDONESIA - Muhammad Abduh, Ikmal Hadi; Dayyan, Muhammad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
Conceptually in the ijârah contract 'ala al-'amâl, the work agreement must clearly specify the object of work and the wages. In the implementation of agreements with Sharia Proofreading Institutions, their services are classified into six forms by unilaterally setting service fees but in reality raises potential formatted problems, namely how to determine proofreading service fees at LSP IAIN Zawiyah Cot Kala Langsa? How is the fulfillment of LSP's obligations for proofreading services with various journal qualifications and review of ijârah 'ala al-'amâl contracts on costs and their correlation with proofreading services. This study uses a normative empirical approach with descriptive analysis research types and interview and documentation collection techniques. The result of his research is that the costing system is carried out unilaterally by the LSP according to the classification of its services. The fees that consumers have to pay are determined based on six types of LSP services, namely full services, template editing services, citation services, translation services, paraphrasing services and article submission services. LSP management provides service guarantees in accordance with contract dictums and SOPs that have been set internally in serving consumers on the use of proofreading services. consumer. Even though the fee is set unilaterally by the LSP management, in principle the entire operational mechanism of LSP is in accordance with the provisions of the ijârah 'ala al-'amâl contract, and ujrah obtained by fiqhiyyah is valid as income for proofreading services which does not conflict with the basic principles of fiqh muamalah.